2002
DOI: 10.1128/jcm.40.8.3004-3011.2002
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping and Genotyping of Sporothrix schenckii Isolates According to Geographic Origin and Clinical Form of Sporotrichosis

Abstract: Sporotrichosis is a subcutaneous mycosis especially frequent in Latin American countries with temperate and tropical climates. Due to the presence of Sporothrix schenckii fungal elements in vegetative matter, this disease is associated with different occupations such as gardening, forestry, and fieldwork (3,6,9,11,16,27). In Mexico (MX), Guatemala (GT), and Colombia (CO), it is a relevant mycosis mainly in farmers who work with a variety of vegetation in the field and individuals who manipulate fungus-contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 23 publications
9
64
1
3
Order By: Relevance
“…The band pattern of the US strain was totally different from those of Brazil, which is in accordance with results from other studies of S. schenckii, as well as with other pathogenic fungi, such as Paracoccidioides brasiliensis and Histoplasma capsulatum (Muniz et al 2001, Mesa-Arango et al 2002, Hahn et al 2003. However, the genetic variability or polymorphic patterns found in different geographical areas can also be due to different ecological processes or genetic factors that promote these polymorphisms (Mesa-Arango et al 2002). Moreover, we cannot discard the possibility that new Sporothrix species are associated with the RJ epidemics, as suggested by Marimon et al (2007).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The band pattern of the US strain was totally different from those of Brazil, which is in accordance with results from other studies of S. schenckii, as well as with other pathogenic fungi, such as Paracoccidioides brasiliensis and Histoplasma capsulatum (Muniz et al 2001, Mesa-Arango et al 2002, Hahn et al 2003. However, the genetic variability or polymorphic patterns found in different geographical areas can also be due to different ecological processes or genetic factors that promote these polymorphisms (Mesa-Arango et al 2002). Moreover, we cannot discard the possibility that new Sporothrix species are associated with the RJ epidemics, as suggested by Marimon et al (2007).…”
Section: Discussionsupporting
confidence: 80%
“…At present, no teleomorph is known for S. schenckii (de Beer et al 2003); however, we found, as with previous studies (Mesa-Arango et al 2002, O'Reilly & Altman 2006, Gutierrez-Galhardo et al 2008, some genetic variability in S. schenckii, especially when analysing strains from different countries. The band pattern of the US strain was totally different from those of Brazil, which is in accordance with results from other studies of S. schenckii, as well as with other pathogenic fungi, such as Paracoccidioides brasiliensis and Histoplasma capsulatum (Muniz et al 2001, Mesa-Arango et al 2002, Hahn et al 2003.…”
Section: Discussionsupporting
confidence: 39%
“…), was described, 5,6 many studies have demonstrated high genetic diversity among different clinical isolates. [7][8][9] Marimon et al (2006) 10 demonstrated that the fungus was actually a complex of cryptic species, 10 afterward separated into different phylogenetic species 11,12 including S. schenckii s. str., S. brasiliensis, S. globosa, S. mexicana and S. luriei.…”
Section: Introductionmentioning
confidence: 99%
“…Both the cutaneous and lympho-cutaneous clinical forms can be acquired by injuries, thorns and scratches from animals [82], while pulmonary infection occurs by inhalation of spores. Immunosuppressive therapy contributes to the increased prevalence [83].…”
Section: Sporotrichosismentioning
confidence: 99%